Imagining A Conscientious Economy (The Macau Ricci Institute Journal, 2023)
The multiple layered crises (pandemic, climate change, differences in development, migration pressures, etc.) force us to consider what kind of economic growth we have and what we may need. In this article, I shall attempt to outline some key features of what could be developed in a “Conscientious Economy”. Given the observable diversity among various national responses to the Covid-19 crisis, it is clear that no existing economic model is likely to be sufficient to trigger a global recovery that is both fair to all and sustainable.  This paper will indicate that there are some promising attempts to rethink economics that need further study, and serious efforts at their implementation.  These should become our priority as we seek to overcome the lingering effects of Covid-19.